2018
DOI: 10.21149/8822
|View full text |Cite
|
Sign up to set email alerts
|

Percepción del peso corporal y la probabilidad de desarrollar obesidad en adultos mexicanos

Abstract: It is very relevant that individuals, regardless of the state of their weight, have an accurate perception of their body and the consequences to their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
4
0
9
Order By: Relevance
“…As risk factors for its development, they found that being a woman (OR= 1.46, p=0.01), having abdominal obesity (OR = 1.69, p<0.01) and perceiving obesity as a "serious" condition (OR = 2.39, p=0.01) were positively related to the correct perception of body weight. On the other hand, age (OR = 0.99, p<0.01), living in rural areas versus urban areas (OR = 0.76, p=0.04) and being overweight (OR = 0.36, p<0.01) or obese (OR = 0.05, p<0.01) versus having a normal weight were negatively related to a correct perception of weight [31].…”
Section: Discussionmentioning
confidence: 96%
“…As risk factors for its development, they found that being a woman (OR= 1.46, p=0.01), having abdominal obesity (OR = 1.69, p<0.01) and perceiving obesity as a "serious" condition (OR = 2.39, p=0.01) were positively related to the correct perception of body weight. On the other hand, age (OR = 0.99, p<0.01), living in rural areas versus urban areas (OR = 0.76, p=0.04) and being overweight (OR = 0.36, p<0.01) or obese (OR = 0.05, p<0.01) versus having a normal weight were negatively related to a correct perception of weight [31].…”
Section: Discussionmentioning
confidence: 96%
“…Perception of the health state, the body image or those traits of distortion or dissatisfaction that suggest a higher weight could have a determinant incidence in life styles that are operationally linked to unhealthy weight loss actions, as long as the body imaginary remains bound to a thin silhouette according to stereotype-based standards of our time; a condition that implies the connection with increased, and further growing, prevalence values in such a vulnerable sector of the population as the adolescent and young people are (17).…”
Section: Discussionmentioning
confidence: 99%
“…The trends of increasing prevalence of overweight and obesity are related to the challenge of combatting the diabetes epidemic in Mexico. Between 1999 and 2016, the combined prevalence of overweight and obesity among Mexican adult women increased from 61.0% to 73.8%; among girls ages 5 to 11 it increased from 22.8% to 32.8%; and for adolescent women ages 12 to 19 it increased from 28.3% to 39.2% (Shamah-Levy et al, 2018;Uribe-Carvajal et al, 2018). Despite the high prevalence of overweight and obesity in 1999, the situation has worsened over time.…”
Section: A Overweight and Obesitymentioning
confidence: 99%